Book Reviews (Historia, 2021)
1. Major, J.: The Contemporary world. A historical introduction 2. Zeeveld, W. G.: Foundations of Tudor Policy 3. Evans, D., Deeming, T. J., Evans, B. en Goldfarb, S.: Herschel at the Cape, 1834-1838 4. Mathew, D.: Lord Acton find his Times 5. Wirt, G. (red.): Asia Handbook6. Fransen, H.: Architectural Beauty of the Old Cape as seen by Arthur Elliott7. Mitchison, R.: A History of Scotland 8. Chadwick, J.: International Organizations 9. Rosenthal, E.: South Africa's Oil search down the Years  10. Levin, N. G.: Woodrow Wilson and World Politics: Americp's Response to War and Revolution  11. Amott, B.: Lippy Lipschitz, a Biography and Catalogue raisonne